2015
DOI: 10.1186/s40594-015-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning to teach scientific practices: pedagogical decisions and reflections during a course for pre-service science teachers

Abstract: Background: This auto-ethnographic study describes research conducted in a science teacher education program at a state university in Turkey, where I had taught the 'laboratory applications' course for the four previous years. While the students learned the basic skills needed to implement a laboratory course, I detected some deficiencies in their understanding of scientific practices. Consequently, I decided to adopt a different approach. In the fall of 2013 to 2014, I participated in a project aimed at impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…The broadening of the perceptions of the participants from both England and Turkey in the short duration of the focus group discussions suggest that the use of visual tools about NOS and opportunities for discussion may be crucial elements in the design of teacher education interventions with the aim of facilitating comprehensive account of NOS. In Saribas and Ceyhan's (2015) study, the effect of the visual tool on scientific practices developed by Erduran and Dagher (2014) was investigated. As a result of introducing this visual tool, researchers found the use of visuals to be supportive of pre-service teachers' representations of NOS.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The broadening of the perceptions of the participants from both England and Turkey in the short duration of the focus group discussions suggest that the use of visual tools about NOS and opportunities for discussion may be crucial elements in the design of teacher education interventions with the aim of facilitating comprehensive account of NOS. In Saribas and Ceyhan's (2015) study, the effect of the visual tool on scientific practices developed by Erduran and Dagher (2014) was investigated. As a result of introducing this visual tool, researchers found the use of visuals to be supportive of pre-service teachers' representations of NOS.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In response to recommendations about the need to engage preservice teachers in scientific practices and the lack of the enactment of such practices in science classrooms, in the study reported in this paper, we explored the use of scientific practices with special emphasis on model-based inquiry in the training of secondary school teachers. The teaching sequence presented in these manuscript, places preservice teachers as learners (i.e., they experience learning of scientific content through scientific practices) and as thinkers (i.e., they reflect on the process experienced, the conceptual and procedural contents learned and the emotions felt in each activity) emphasizing the integration of scientific practices into lesson planning and teaching (Saribas and Ceyhan 2015). Hence, one contribution of this study is that it adds to the limited existing knowledge base on scientific practices by offering a concrete example of the design and implementation of a teaching sequence in the context of secondary science teacher education.…”
Section: Discussionmentioning
confidence: 99%
“…They disagreed with scientists deny imagination and creative thinking to explore new knowledge; scientific knowledge or explorations are products of scientists, needs of society and community culture are not related; scientists work in their laboratory, even though social needs are not influence to scientists; we use process of science for making a consideration of which picture in gallery is the best; scientist works in lonely under setting laboratory, if many scientists may be difficult to conclude; scientists do research by taking responsibility to benefits than those moral and ethics-that are nature of science through scientific world view and scientific inquiry. That is, the two prongs of objectivist and subjectivist concepts lead understanding nature of science to the world [15][16][17][18][19]. However, some items that they rated disagreescientific knowledge comes from experiments only; scientists employed only creative thinking for designing innovations and inventions; and scientists are social partners, on behalf of expertise who understand and criticize on phenomena even though no more showing opinions and feelings-it seems misconception about nature of science.…”
Section: Resultsmentioning
confidence: 99%